2004
DOI: 10.21000/jasmr04010334
|View full text |Cite
|
Sign up to set email alerts
|

Acidity and Alkalinity in Mine Drainage: Practical Considerations

Abstract: Abstract. In this paper, we emphasize that the Standard Method hot peroxide treatment procedure for acidity determination (hot acidity) directly measures net acidity or net alkalinity, but that more than one water-quality measure can be useful as a measure of the severity of acid mine drainage. We demonstrate that the hot acidity is related to the pH, alkalinity, and dissolved concentrations of Fe, Mn, and Al in fresh mine drainage. We show that the hot acidity accurately indicates the potential for pH to decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Even though metals were not speciated except to differentiate Fe II from Fe III , the calculated acidity produced by Equation 9 matched several hundred measured Hot Acidities reasonably well, although less well at higher acidities (Hedin et al, 1994). Hedin et al (1994) suggest that even at low pH (2.7), H + acidity is only a minor component (compared to metals) of total acidity based on Equation 9.…”
Section: Calculation Of Theoretical Aciditymentioning
confidence: 84%
See 2 more Smart Citations
“…Even though metals were not speciated except to differentiate Fe II from Fe III , the calculated acidity produced by Equation 9 matched several hundred measured Hot Acidities reasonably well, although less well at higher acidities (Hedin et al, 1994). Hedin et al (1994) suggest that even at low pH (2.7), H + acidity is only a minor component (compared to metals) of total acidity based on Equation 9.…”
Section: Calculation Of Theoretical Aciditymentioning
confidence: 84%
“…Stumm and Morgan (1996) Acidity from the alkalinity gives a net alkalinity result that is incorrect and can result in inadequate addition of alkaline materials such as lime or limestone in mine-drainage treatment. Hedin et al (1994) …”
Section: Laboratory Definitions Of Alkalinity and Aciditymentioning
confidence: 99%
See 1 more Smart Citation
“…The equivalents of acid used to decrease pH to 4 are subtracted from the equivalents of base added in titrating to pH 8.3, making the result essentially a net acidity. Cravotta and Kirby (2004), Cravotta (2005a, 2005b) and Hedin (2006) showed that a reliable net acidity can be obtained from the hot peroxide acidity (Standard Methods, 1998), or by calculation from the pH, Fe, Al, Mn and alkalinity concentrations:…”
Section: Aciditymentioning
confidence: 99%
“…Cravotta and Kirby (2004) urged labs and others to use the Standard Methods (1998) procedure and to report negative acidities when obtained.…”
Section: Aciditymentioning
confidence: 99%